Design and Fabrication of a PDMS-Based Manual Micro-Valve System for Microfluidic Applications - Tu N. Le; Van-Anh Nguyen; Giang L. Bach; Lam D. Tran; Ha H. Cao (Advances in Polymer Technology)
In this study, a manual micro-valve system (dimension: w × h: 1000 × 50 μm with 8-integrated channel valves was designed for controlling up to 8 different flows of agents (including magnetic nanoparticle flow) injected into the mixture zone of the microfluidics. The working parts of the micro-valve and microfluidic channel were fabricated from Poly(dimethyl siloxane) materials. The aperture of each channel valve was manually manipulated by a screw and a support kit (made of Plexiglas® materials). This valve system was connected to a microfluidic device with two important modules: a multi-liquid mixing component and a micro-reactor (~5 μL of volume). The study on controlling liquid flows proved that this valve system was effective for the experiments on the flow mixing and delivering the reactants into the micro-reaction chamber in order. The results are the first step for the fabrication of liquid flow controllers in integrated microfluidic systems towards biological analysis applications.